(NkW)QÆLÆNG ZAHOPL@Ã Æ ROZWIWAÃ (B:s)E (NGURTK(B. (NROBOTA Z)QÆ ST(B. (NDO[KÆLXNQTAMI (B/s)E - (NnAUMOWA(B, (NaNTON)QÆNA(B,s)E (2015)
(NpODANO OR)QÆÃNTOWNIJ PERSPEKTIWNIJ PLAN GURTKOWOÇ ROBOTI(B.s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NmETODIKA NAW^ANNQ W DO[K)QÆLXNIH NAW^ALXNIH ZAKLADAHs)E -- (NTRUDOWE NAW^ANNQs -- (NGURTKIs -- (NuKRA)QÇNAs)E; (NgURTKOWA ROBOTAs -- (NSTAR[)QÆ DO[KÆLXNIKIs)E; (NMETODIKA NAW^ANNQs; (NTRUDOWE NAW^ANNQs; (NROBOTA Z PAPEROMs; (NKW)QÆLÆNGs)E; (NGURTKIs; (NSTAR[)QÆ DO[KÆLXNIKIs)E; (NPAPEROPLASTIKAs; (NGURTKOWA ROBOTAs